Pemanfaatan Tanaman Eceng Gondok Menjadi Kerajinan Anyaman Sebagai Upaya Dalam Mengurangi Pencemaran Sungai Di Kecamatan Pammana - Sitti Rahmiyanti; Rosmini Maru; Nathaniel Lucky Mangngesak; Alya Nurul Mutmainnah; Rini Handayani (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
In Pammana Subdistrict there are very many water hyacinth plants and have the potential to damage the environment. In this study, we intend to clean the river from water hyacinth plants as well as to process these plants into something useful. For this reason, the researchers carried out this activity with the objectives of: 1.) socializing the Pammana residents about the importance of protecting the environment, especially the rivers in Pammana, 2) Conducting training to the community regarding the use of water hyacinth into wickerwork, 3) Knowing the use of water hyacinth plants as woven crafts in reducing river pollution in Pammana District. The methods used to solve this problem are descriptive analysis, observation, interviews, discussions, and training assistance in making water hyacinth woven crafts with the target group. The processing processes are: Drying water hyacinth, making patterns, weaving, sewing, and finishing. The results of the activities achieved were: 1.) Increased awareness of Pammana residents regarding the importance of protecting the environment, especially rivers in Pammana, 2.) There was an increase in community creativity, especially in managing water hyacinth into woven crafts, 3.) Utilization of water hyacinth into woven crafts was very effective in reducing growth of water hyacinth in the river Pammana District